Cannabis Use and Brain Volume in Adolescent and Young Adult Cannabis Users: Effects Moderated by Sex and Aerobic Fitness. (July 2021) - Sullivan, Ryan M.; Wallace, Alexander L.; Wade, Natasha E.; Swartz, Ann M.; Lisdahl, Krista M.
Abstract: Objectives: Studies examining the impact of adolescent and young adult cannabis use on structural outcomes have been heterogeneous. One already-identified moderator is sex, while a novel potential moderator is extent of aerobic fitness. Here, we sought to investigate the associations of cannabis use, sex, and aerobic fitness levels on brain volume. Second, we explored brain–behavior relationships to interpret these findings. Methods: Seventy-four adolescents and young adults (36 cannabis users and 38 controls) underwent 3 weeks of monitored cannabis abstinence, aerobic fitness testing, structural neuroimaging, and neuropsychological testing. Linear regressions examined cannabis use and its interaction with sex and aerobic fitness on whole-brain cortical volume and subcortical regions of interests. Results: No main-effect differences between cannabis users and nonusers were observed; however, cannabis-by-sex interactions identified differences in frontal, temporal, and paracentral volumes. Female cannabis users generally exhibited greater volume while male users exhibited less volume compared to same-sex controls. Positive associations between aerobic fitness and frontal, parietal, cerebellum, and caudate volumes were observed. Cannabis-by-fitness interaction was linked with left superior temporal volume. Preliminary brain–behavior correlations revealed that abnormal volumes were not advantageous in either male or female cannabis users. Conclusions: Aerobic fitness was linked with greater brain volume and sex moderated the effect of cannabis use on volume; preliminary brain–behavior correlations revealed that differences in cannabis users were not linked with advantageous cognitive performance. Implications of sex-specific subtleties and mechanisms of aerobic fitness require large-scale investigation. Furthermore, present findings and prior literature on aerobic exercise warrant examinations of aerobic fitness interventions that aimed at improving neurocognitive health in substance-using youth.